268 EFFECTS OF METALLOPORPHYRINS ON SURVIVAL OF MICE FOLLOWING ORAL SALMONELLA INFECTION. (1st January 2005) - Burns, S. M.; Wong, R. J.; Contag, C. H.; Stevenson, D. K.
Abstract : Heme oxygenase (HO) is the rate-limiting enzyme in the degradation pathway of heme producing biliverdin, carbon monoxide (CO), and iron. There are two well-described isozymes of HO, the constitutive HO-2 and inducible HO-1. HO-1 is induced by heme, stress, lipopolysaccharide (LPS), and heavy metals and reported to mediate anti-inflammatory processes. However, the exact role of HO-1 in mediating host response to infection is unknown. In addition, clinical trials have begun evaluating the safety and efficacy of metalloporphyrins (Mps), competitive inhibitors of HO, as potential therapeutic compounds for the treatment of neonatal jaundice. In this study, we evaluated whether the administration of Mps prior to oral infection with Salmonella typhimurium affects susceptibility and/or alters the course of infection. 6-wk old adult FVB mice were administered 150 μL of vehicle or 30 μmol/kg body weight of SnMP or ZnBG by gavage feeding 3 hours prior to oral inoculation with a lethal dose of 107 colony-forming units of S. typhimurium SL1344 (n = 15 - 20). Morbidity and mortality of mice was then followed for 21 days and Kaplan-Meier plots were constructed. Using the logrank sum (Mantel-Cox) test, we found that survival rates in mice treated with SnMP or ZnBG were significantly poorer than that of infected control mice (p ≤ 0.05). These results demonstrate that Mp treatment may increase susceptibility and alter the course of infection due to its inhibition on tissue HO and heme degradation. These observations suggest that HO-1 may play a protective role in host response. More importantly, it also raises concerns about the routine or repetitive use of Mps in human newborns for the treatment of neonatal jaundice, especially in those infants, who are infected.